Representasi Arketipe Carl Gustav Jung Tokoh Utama Dalam Novel Anwar Tohari Mencari Mati Karya Mahfud Ikhwan - Adi Roadi; Zilva Mardadila Ililirugun; Eva Dwi Kurniawan (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to describe the personality archetypes of the main character in the novel entitled Anwar Tohari Looking for Death by Mahfud Ikhwan. This research is qualitative research in the form of descriptive data collection methods, namely reading and note-taking techniques as well as analyzing sentences in the novel. This research uses a psychological perspective with Carl Gustav Jung's psychoanalytic theory, namely the theory of archetypal levels of the psyche including; Mask (persona). Shadow (shadow), Anima, Hero (hero), Self (self). The research results show that the character Anwar has a different personality from other characters, Anwar has a personality that was created by Jung's character, namely Mask (persona), Shadow (shadow), Anima, Pahlawan (hero), and Diri (self).